Empowerment of Farmer Group in Bioconversion of Organic Waste Management with Utilization of Black Soldier Fly Larvae Become Organic Fertilizer â€œKasgotâ€ - Sebayang, Nur Ulina Warnisyah; Sipayung, Antonio Marro; Ayu, Putri Chandra; Sinamo, Karina Nola (Talenta Publisher, 2022)
The amount of organic waste in the form of cow, poultry, goat manure, and fruit and vegetable waste that is no longer suitable for consumption has the opportunity to be reprocessed into a product that can be reused in Sidomulyo Village. The lack of awareness and knowledge of the farmer group community to process organic waste is one of the factors causing the accumulation of organic waste so that it becomes useless and can pollute the environment. In addition, organic waste processing can also be used as a way to promote zero waste in the village environment. One of the innovations that can be applied and utilized by farmers in processing organic waste and producing organic fertilizer with the best quality is bioconversion by utilizing maggot or larvae from BSF (Black Soilder Fly) flies which are able to decompose organic waste in a fairly short time because maggots are animals. greedy in consuming their feed (organic waste). The purpose of this activity is to assist farmers in processing organic waste. This activity resulted in product innovation in the form of cassava fertilizer which can be reused by farmers as organic fertilizer and can be used as animal feed.